Risk, crisis, and disaster management in small and medium-sized tourism enterprises - Toubes, Diego R. 1966-; Araújo Vila, Noelia 1983- (A volume in the Advances in hospitality, tourism, and the services industry (AHTSI) book series, 2021)
"This book connects the challenges of today's tourism industry more closely to academic research, connecting research in the field of crisis management with the risks affecting small and medium-sized tourism enterprises" - Provided by publisher